Thermodynamics and Solution Studies on Some Quaternary Metal Complexes and their Comparison with Binary and Ternary Complexes - D. Patel, Dhara; Sharma, Sangita; Patel, K.R.; Patel, V.D. (Asian Journal of Chemistry, 2011)
Equilibrium studies on quaternary metal complexes of type M1M2AB where M1 and M2 are Cu(II) and Ni(II) or Cd(II) or Co(II) or Pb(II), L1 = o-phenylenediamine and L2 = salicylic acid were carried out using Irving Rossotti titration technique at 30 ± 0.1, 40 ± 0.1 and 50 ± 0.1 ºC at fixed ionic strength, μ = 0.2 mol dm-3 (NaClO4). The separation of titration curves demonstrate the formation of mixed metal mixed ligand complexes of stoichiometry M1M2L1L2. All metal ion formation constant of the complexes, M1M2L1L2 in addition to M1L1L2, M2L1L2, M1(L1)2, M1(L2)2, M2(L1)2 and M2(L2)2 type of complexes for all metal ions were evaluated using for the Fortran IV computer program and the complex formation equilibrium data were pruned with the aid of speciation curves plotted with aid of Fortran IV computer program SPEPLOT. The stability order of metal complexes and solution structure of heterobinuclear M1M2L1L2 complexes have been discussed on the basis of basicity of ligands and coordination sphere of complexation.